EFFECTIVENESS OF HYPOTHERMIC THERAPY IN PATIENTS STOP HEART POST: LITERATURE REVIEW - Mardiana, Mardiana; Mas'ud, Alfian (Universitas Respati Yogyakarta, 2021)
Cardiac arrest has become one of the most unexpected, dramatic, and life-threatening events in the world of health. The increase in the number of patients who survived after cardiac pulmonary resuscitation has increased as more cardiopulmonary resuscitation training and defibrillation equipment are becoming easier to carry to various locations, but brain damage begins within minutes of cardiac arrest with the consequence of patients having their hearts beating again. and hospitalized unable to leave the hospital or in a vegetative state. Hypothermic therapy has been used frequently in cardiac surgery for several years for neurological protection. The data-based used in making this literature review are Google Scholar and Proquest. The keywords used in the search for articles on google scholar are